Androgen derivatives improve blood counts and elongate telomere length in adult cryptic dyskeratosis congenita. (3rd August 2020) - Kirschner, Martin; Vieri, Margherita; Kricheldorf, Kim; Ferreira, Monica S. Ventura; Wlodarski, Marcin W.; Schwarz, Michaela; Balabanov, Stefan; Rolles, Benjamin; Isfort, Susanne; Koschmieder, Steffen; Höchsmann, Britta; Panse, Jens; et al.
Summary: Dyskeratosis Congenita (DKC) is a systemic disorder caused by mutations resulting in impaired telomere maintenance. Clinical features include bone marrow failure and an increased risk of developing hematological malignancies. There are conflicting data whether androgen derivatives (AD) can elongate telomeres in vivo and whether AD treatment enhances the risk of gaining myelodysplastic syndrome‐related mutations. Seven TERC or TERT ‐mutated DKC patients underwent AD treatment. All patients revealed hematological response. Telomere length of lymphocytes and granulocytes increased significantly and no MDS‐related mutations were detected. Pending longer follow‐up, treatment with AD seems to represent an efficient and safe therapy for DKC patients.